1993
DOI: 10.1093/oxfordjournals.aje.a116679
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Headaches in Relation to Proximity of Residence to an Alternating-Current Transmission Line Right-of-way

Abstract: Electric power transmission lines have become objects of public controversy. Hypotheses have linked neurobehavioral effects to the electric and magnetic fields that these lines produce. The authors conducted a telephone interview survey in November 1987 to assess the prevalence of depressive symptoms and headache in relation to proximity of residence to an alternating-current transmission line in the United States. Proximity to the line, defined as residing on a property abutting the right-of-way or being able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Baris et al [1996] reported evidence for an association between suicide and cumulative electric-field exposure. A correlation between EMF residential exposure and depression was suggested by other studies [Dowson and Lewint, 1988;Perry et al, 1989;Poole et al, 1993], but no correlation was found by McMahan et al [1994]. Wilson [1988] suggested that the possible disruption by ELF-field exposure of the natural circadian rhythms of melatonin could be linked to depression. No association was found between occupational exposure to electric fields and symptoms of depression in 390 electric power transmission and distribution workers [Broadbent et al, 1985].…”
Section: Neurologic and Psychiatric Diseasesmentioning
confidence: 91%
“…Baris et al [1996] reported evidence for an association between suicide and cumulative electric-field exposure. A correlation between EMF residential exposure and depression was suggested by other studies [Dowson and Lewint, 1988;Perry et al, 1989;Poole et al, 1993], but no correlation was found by McMahan et al [1994]. Wilson [1988] suggested that the possible disruption by ELF-field exposure of the natural circadian rhythms of melatonin could be linked to depression. No association was found between occupational exposure to electric fields and symptoms of depression in 390 electric power transmission and distribution workers [Broadbent et al, 1985].…”
Section: Neurologic and Psychiatric Diseasesmentioning
confidence: 91%
“…Other effects which have been observed include disturbances of sleep [2], a deterioration of cerebral activity [3,4], changes in the permeability of the meninges [5], an increase in blood pressure [6], induction of stress [7], hormonal disturbances [8][9][10] and carcinogenic changes [11][12][13]. Similarly, papers have been published which attracted the attention of scientists and the population in general and which purported to show a relationship between exposures to ELF and an increase in certain health risks such as cancer [14,15], abortion [16,17], suicide and depression [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Moreover, exposure to EMFs has been linked with depression and depressive tendencies. [13][14][15][16][17][18] Finally, there is strong evidence that depressive illness is an important risk factor for suicide. 3,4 We conducted a case-control study to consider the risk of suicide for electric utility workers for whom individual estimates of exposure to magnetic fields were obtained based on job titles.…”
mentioning
confidence: 99%